Bis-morpholinophosphorylchloride, a novel reagent for the conversion of primary amides into nitriles. (2nd February 2021) - Rao, P. Purnachandra; Nowshuddin, Shaik; Jha, Anjali; Rao, B. Leela Maheswara; Divi, Murali K.; Rao, M.N.A.
Graphical abstract: Highlights: Easy workup. Simple and mild conditions. No racemization. Stable solid reagent. Abstract: Bis-morpholinophosphorylchloride (Bmpc), in the presence of a base, is an efficient dehydrating agent for both aromatic and aliphatic primary amides, and gives corresponding nitriles under mild conditions in god yields and purity. During the reaction the enantiomeric integrity remains intact.